Determinants of Contemporary Sharia Financial Literacy among Students in Higher Education Institutions - M Rizwan; Eriyati; Yelly Zamaya (EKONOMIKA SYARIAH : Journal of Economic Studies, 2025)
This research aims to analyze the determinants of contemporary Sharia financial literacy among students of the Faculty of Economics and Business at Universitas Riau (FEB UNRI). This study employs a quantitative approach, using numerical data derived from both primary and secondary sources. Primary data were collected through questionnaires using a Likert scale, distributed to 304 students from the Development Economics, Accounting, and Management study programs. Secondary data were obtained from literature reviews, academic journals, websites, and publications from financial and statistical institutions. The data analysis method used was Multiple Linear Regression with the SEM-PLS (Structural Equation Modeling–Partial Least Squares) approach. The results indicate that education, information media, and the role of clerics/government have a significant and positive effect on Sharia financial literacy,while the social environment has a positive but insignificant effect. The primary contribution of this study is to emphasize the importance of enhancing Sharia financial literacy among students as part of preparing the younger generation to support the development of a more advanced Islamic economic system in the future. Studi ini bertujuan untuk menguji determinan literasi keuangan syariah kontemporer mahasiswa Fakultas Ekonomi dan Bisnis Universitas Riau (FEB UNRI). Studi dilakukan dengan metode kuantitatif dengan data berbentuk numerikal. Studi menggunakan data kuantitatif berupa data primer dan data sekunder. Data primer menggunakan hasil wawancara dan kuesioner dengan skala likert pada mahasiswa FEB UNRI yang berjumlah 304 orang yang berasal dari Program Studi Ekonomi Pembangunan, Akuntansi dan Manajemen. Sedangkan data sekunder berupa data yang tersedia dari studi literatur, jurnal, website, terutama dari lembaga keuangan dan statistik. Metode analisis data adalah regresi linier berganda menggunakan model SEM-PLS. Temuan mengungkap bahwa Pendidikan, media infromasi, dan peran ulama/pemerintah berpengaruh signifikan dan positif, dan terakhir lingkungan sosial berpengaruh tidak signifikan dan positif, terhadap literasi keuangan syariah pada mahasiswa FEB UNRI. Kontribusi utama dalam studi adalah untuk meningkatkan khazanah ekonomi dan keuangan syariah saat ini kepada mahasiswa sebagai generasi muda untuk masa depan dan untuk mengembangkan ekonomi yang lebih maju.